THE ROLE OF INCLUSIVE LEADERSHIP IN PROVIDING QUALITY EDUCATION FOR ALL IN ISLAMIC SECONDARY EDUCATION INSTITUTIONS - Sarwo Edy; Sumarta Sumarta; Jaedi Jaedi (International Journal Labs, 2024)
In the contemporary landscape of education, the imperative of providing quality education for all has become a paramount concern. This dissertation investigates the instrumental role of inclusive leadership in ensuring the provision of quality education for all in Islamic secondary educational institutions. These institutions, serving as bastions of both religious and academic development, demand a leadership approach that is inclusive, equitable, and forward-looking. The study delves into the multifaceted concept of inclusive leadership, exploring its theoretical underpinnings and practical implications within the unique context of Islamic secondary education. Inclusive leadership goes beyond conventional models by actively involving diverse stakeholders, fostering a collaborative and supportive environment, and addressing the individual needs of all students. The research employs a mixed-methods approach, combining qualitative and quantitative analyses to comprehensively understand the impact of inclusive leadership on access to education and the enhancement of learning experiences